AKUNTABILITAS PENGELOLAAN DANA DALAM UPACARA ADAT TETULAK JEBAK MASYARAKAT PRINGGABAYA - Hafiz Kurniawan; Ayudia Sokarina (STIE PENA, 2025)
This study aims to interpret the accountability of fund management in the Tetulak Jebak traditional ceremony. The research was conducted in Pringgabaya Village, East Lombok Regency, West Nusa Tenggara. The approach used is qualitative with an ethnographic method. Informants were deliberately selected by visiting their homes every time they returned from the mosque. The data used in this study are primary data obtained through direct interaction with the community. The results of this study indicate that in every stage of the Tetulak Jebak ceremony, which includes planning, implementation, administration, and accountability, there are values such as: kinship, deliberation, honesty, mutual cooperation, responsibility, and mutual trust. Although there is a sense of mutual trust in the management of customary funds, some educated members of the community feel that transparency in financial reporting has not been fully achieved, especially amid the demands of modernization. Some informants stated that information regarding fund management has not been evenly communicated openly to all community members. The implications of these findings highlight the importance of enhancing transparency in reporting customary ceremony funds to strengthen public trust. In addition, there needs to be a simple reporting system that is easily accessible to all residents.